INTERNALISASI FILOSOFIS KISAH TERPUJI NABI MUHAMMAD SAW DALAM MENUMBUHKAN AKHLAK MULIA - Radjendra, Ryan; Silpa; Siti Khotimah; Saiful Anwar; Siti Zulaikha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores the philosophical values contained in the noble stories of Prophet Muhammad (peace be upon him) as a foundation for moral character development among Muslims. Using a qualitative literature review approach, the study examines the moral and spiritual meanings found in both classical and modern sources. The findings indicate that the Prophet’s stories possess educational strength capable of fostering virtues such as honesty, compassion, patience, and responsibility. These values serve as the basis for moral internalization within Islamic education, addressing the ethical challenges of the modern era. The study emphasizes the importance of integrating the Prophet’s exemplary stories into educational curricula as an effective strategy for shaping the character of the younger generation. Keywords: character, internalization, prophetic stories, Islamic education, philosophical values